卡片教学法对加油汉语补习班小学一年级学生掌握汉语名词的影响 PENGARUH PENGGUNAAN FLASHCARD TERHADAP PENGUASAAN KATA BENDA PADA SISWA DI KURSUS MANDARIN JIAYOU - Wijaya, Kesumawaty; Joan, Cindy (Journal of Language, Literature and Teaching, 2022)
The study aims to find out whether the application of visual learning media in the form of flash cards either has a significant or no effect on the mastery of Chinese nouns in students in the Jiayou Mandarin Course. The research design used is a quantitative research design. The data collection technique used is in the form of a test which amounts to 20 questions with data processing techniques for reliability testing, normality testing, homogeneity testing, and hypothesis testing. The results of the calculation of the reliability test with KR20 obtained a value of 0.710 which means the reliability criteria are high, the Lilliefors Normality Test in the pre-test data for class I-A is 0.198 and class I-C is 0.094 at a significant level = 0.05 of 0.220 which means the data is normally distributed. Homogeneity test of the two data groups with the F test obtained a value of 1.01 at a significant level = 0.05 of 2.48 which means the data is homogeneous. Hypothesis Testing with t-test obtained a value of 7.795. Then the t table obtained at the significant level = 0.05 is 2.131. From these two values, it is found that thitung bigger ttabel (7.795 bigger 2.131). So, it can be concluded that H0 is rejected and Ha is accepted, which means that there is a significant influence between flash card media on noun mastery in class I-SD students of the Jiayou Mandarin Course in Medan.Keywords: influence, use, flash card, mastery, noun, Jiayou mandarin course.